(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
HTML5 brings new features to the web, enriching the user experience. This article aims to analyze the JSF component libraries PrimeFaces and RichFaces regarding such features. The goal is to check whether the libraries make use of the new features, by evaluating the HTML generated by the JSF pages. It was noted that libraries do not generate HTML5 actively, using its own specific components whenever possible. But such behavior can be changed through JSF features. And the PrimeFaces library was more HTML5 generation friendly than RichFaces.